Prevalence of Multidrug-Resistant CTX-M Extended Spectrum Beta-Lactamase-Producing Escherichia coli From Different Bovine Faeces in China - Wei, Xiaojuan; Wang, Weiwei; Lu, Ningning; Wu, Lingyu; Dong, Zhen; Li, Bing; Zhou, Xuzheng; Cheng, Fusheng; Zhou, Kairen; Cheng, Haijian; Shi, Hongmei; Zhang, Jiyu (Frontiers in Veterinary Science, 2022)
To analyse prevalence of CTX-M-producing Escherichia coli in Yak, beef cattle and dairy cattle faeces from different provinces in China, 790 faecal samples from yaks, beef cattle and dairy cows were used. Among all samples, 523 non-duplicate Escherichia coli were identified, and 29.6% of samples harboured CTX-M producers. The results showed that these Escherichia coli harboured 15 clusters of CTX-M genes, they were CTX-M-79, CTX-M-55, CTX-M-15, CTX-M-14, CTX-M-28, CTX-M-179, CTX-M-65, CTX-M-24, CTX-M-27, CTX-M-102, CTX-M-105, CTX-M-173, CTX-M-238, CTX-M-196, and CTX-M-10, respectively. The dominant resistance gene was CTX-M-15, CTX-M-14 and CTX-M-55. Moreover, the distribution of CTX-M genes was related to geographical region. Based on the above findings, we reasoned that the bovines are potential reservoirs of antibiotic resistance, and this problem should be given adequate attention.